Examining exercise intention and behaviour during pregnancy using the Theory of Planned Behaviour: a meta-analysis. (14th March 2016) - De Vivo, M.; Hulbert, S.; Mills, H.; Uphill, M.
Abstract: Background: The efficacy and predictive utility of the Theory of Planned Behaviour (TPB) in explaining a variety of behaviours including physical activity (PA) is well documented. However, the relative contribution of the theory's components in describing intention and behaviour may differ depending on the context, time and population being studied. Such evidence is necessary to inform PA advice and interventions aimed at special populations including pregnant women.Objective: The purpose of this study was to review the existing literature surrounding the application of the TPB in explaining exercise intentions and behaviour during pregnancy and to evaluate the magnitude of relationships between TPB constructs within this context.Method: Multiple search strategies yielded 99 potentially relevant studies of which 47 were assessed against the inclusion criteria. Finally, eight studies were subjected to a random-effects meta-analysis.Result: Results confirmed the existence of a strong relationship between intention and behaviour while perceived behavioural control (PBC) revealed a weaker correlation with behaviour. Women's attitude towards exercise had the strongest association with their intention to be physically active while expecting. However, both PBC and subjective norm showed strong relationships with intention.Conclusion: The study supports the TPB as a relevant conceptual framework for the investigation of PA intentions and behaviours during pregnancy. Furthermore, this study supported subjective norm as a pertinent construct to investigate exercise intentions and behaviour in a pregnant population. These findings present both researchers and practitioners with an opportunity for intervention and further research.